Regulation of c-Src activity by the expression of wild-type v-Src and its kinase-dead double Y416F-K295N mutant - Vojtechová, Martina; Senigl, Filip; Sloncová, Eva; Tuhácková, Zdena (Archives of biochemistry and biophysics, 2006)
Active, wild-type v-Src and its kinase-dead double Y416F-K295N mutant were expressed in hamster fibroblasts. Expression of the active v-Src induced activation of endogenous c-Src and increased general protein-tyrosine phosphorylation in the infected cells. Expression of the kinase-dead mutant induced hypophosphorylation of Tyr416 of the endogenous c-Src. The inactivation of c-Src was reversible, as confirmed by in vitro kinase activity of c-Src immunoprecipitated from the kinase-dead v-Src-expressing cells. Both activation and inactivation of c-Src may be explained by direct interaction of the v-Src and c-Src that may either facilitate transphosphorylation of the regulatory Tyr416 in the activation loop, or prevent it by formation of transient dead-end complexes of the Y416F-K295N mutant with c-Src. The interaction was also indicated by co-localization of v- and c-Src proteins in immunofluorescent images of the infected cells. These results suggest that dimerization of Src plays an important role in the regulation of Src tyrosine kinase activity.
Keywords: mutace; CSK Tyrosine-Protein Kinase; aktivace enzymů; Gene Expression Regulation, Enzymologic; buněčné linie; regulace genové exprese enzymů; Enzyme Activation; Fibroblasts; mutageneze cílená; Structure-Activity Relationship; lidé; Mutation; fibroblasty; Oncogene Protein pp60(v-src); Mutagenesis, Site-Directed; Cell Line; skupina kinas odvozených od src-genu; src-Family Kinases; C-terminální Src kinasa; vztahy mezi strukturou a aktivitou; onkogenní protein pp60(v-src); Protein-Tyrosine Kinases; tyrosinkinasy; Humans